518 A Comparison of Outcomes After Analgesic and Anti-Inflammatory Injections into The TMJ After Arthroscopy and Arthrocentesis. (12th October 2021) - Goel, A; Tahim, A; Komath, D
Abstract: Introduction: Temporomandibular joint dysfunction (TMJD) affects 12% of the population, with up to 5% seeking help for their symptoms. Minimally invasive TMJ surgery techniques have been harnessed by Oral and Maxillofacial surgeons to directly visualise joint pathology, facilitate joint arthrocentesis and enable safe injection of analgesic and anti-inflammatory agents into the joint space. This study compares outcomes after injection of either morphine or protein-rich plasma (PRP) after TMJ arthroscopy and arthrocentesis. Method: Consecutive patients between 2017-2020 undergoing either morphine or PRP injections after TMJ arthroscopy and arthrocentesis were retrospectively reviewed. Basic demographics and Wilkes score were noted. All patients underwent a trial of conservative management prior to any surgical intervention. Pre- and post-operative mouth opening was measured objectively (mm), while pre- and post-operative pain scores were noted using standard subjective pain scores (1-10). Results: 31 patients underwent TMJ injections with morphine (n = 18) or PRP (n = 13) after TMJ arthroscopy and arthrocentesis. Both groups showed a significant reduction in subjective pain scores post-operative ( p < 0.05). Patients receiving PRP injections showed greater mouth opening scores (4.0mm change in MO for PRP vs 1.7mm change in MO for morphine) . Conclusions: PRP shows to be as effective in pain management of patients with TMJD undergoing arthroscopy and arthrocentesis as morphine. The increase in mouth opening in patients receiving PRP injection could be attributed to the anti-inflammatory potential of PRP. These findings suggest that further evaluation of the benefits of PRP use in TMJD is warranted.